The impact financial resources on implementation of large-scale electronic health records in the Saudi Arabia's primary healthcare centers: Mixed methods - Alzghaibi, Haitham; Mughal, Yasir Hayat; Alkhamees, Mohammad; Alasqah, Ibrahim; Alhlayl, Adel Sulaiman; Alwheeb, Mohammed Hamed; Alrehiely, Majedah (Frontiers in Public Health, 2022)
There is worldwide demand for the implementation of electronic health systems and a transformation to electronic transactions in healthcare organisations. This move to e-health transformation stems from the perceived positive impact that e-health systems have in improving the quality of healthcare and, in turn, reducing expenses. Despite this, more than half of previous Electronic Health Record System (EHRS) implementation projects have failed due to several barriers and challenges such as cost. Aim of the study: To evaluate the impact of financial resources (FR) on the implementation of the EHRS in PHCs in SA. Methods: A mixed methods approach was implemented. SPSS and AMOS-SEM are used to test reliability and validity and hypotheses. Thirty-one (59%) out of 51 policy makers at the MoH filled and returned the questionnaire while 13 policymakers were interviewed using semi-structure interviews. Results: results revealed that both measurement model and structural models met the threshold. All scales are found reliable and valid. Furthermore financial resources have positive impact on EHRS implementation. Findings from both studies show that financial resources have a very positive impact to facilitate large-scale EHRs implementation and overcome barriers that may lead to the failure of the project.